Research on language learning motivation in school settings in System. (July 2022) - Zhang, Fang; Wang, Jinquan; Mairin, Hennebry-Leung
Abstract: This review of System's scholarship on school-based language learning motivation focuses on 12 papers on learners and teachers in secondary school settings. Of 190 studies on motivation published in the Journal from 1990 to 2021, 24 have had a focus on secondary school contexts. The 12 focus studies are drawn from these. The review highlights theoretical and methodological shifts that have characterized the field of language learning motivation and considers the extent to which these are manifested in the Journal's scholarship, specifically pointing to a growing concern for approaches that account for the complex, dynamic, and situated nature of motivation. Studies on language learning motivation in school settings have addressed a range of aspects including motivational change, the interplay between instructional approaches and motivation, the role of sociocultural context in shaping and directing learner motivation, teacher cognition on motivation, and teachers' motivation for language teaching. While acknowledging the extensive body of literature on language learning motivation among adult learners, the review concludes with suggestions for ways in which the still rather limited knowledge about school-based motivation could be extended and enriched.